Does Ras Activate Raf and PI3K Allosterically? - Nussinov, Ruth; Tsai, Chung-Jung; Jang, Hyunbum (Frontiers in Oncology, 2019)
The mechanism through which oncogenic Ras activates its effectors is vastly important to resolve. If allostery is at play, then targeting allosteric pathways could help in quelling activation of MAPK (Raf/MEK/ERK) and PI3K (PI3K/Akt/mTOR) cell proliferation pathways. On the face of it, allosteric activation is reasonable: Ras binding perturbs the conformational ensembles of its effectors. Here, however, we suggest that at least for Raf, PI3K and NORE1A (RASSF5), that is unlikely. Raf’s long disordered linker dampens effective allosteric activation. Instead, we suggest that the high-affinity Ras–Raf binding relieves Raf’s autoinhibition, shifting Raf’s ensemble from the inactive to the nanocluster-mediated dimerized active state, as Ras does for NORE1A. PI3K is recruited and allosterically activated by RTK (e.g. EGFR) at the membrane. Ras restrains PI3K’s distribution and active site orientation. It stabilizes and facilitates PIP2 binding at the active site and increases the PI3K residence time at the membrane. Thus, RTKs allosterically activate PI3Kα; however, merging their action with Ras accomplishes full activation. Here we review their activation mechanisms in this light and draw attention to implications for their pharmacology.